Microbiological and Physico-Chemical Analysis in Potable Water from Different Sources via Elite Regions of Meghalaya, India - Nongrum, Sumi; Lyngdoh, Wadamika (International Journal of Scientific Research in Biological Sciences, 2022)
Introduction: Quality of drinking water is one of the major concern in the Globe. Drinking water should be free from pathogens and within limit of physico chemical parameters such as pH, chloride, alkalinity etc., for preventing diseases and improving quality of life. Objectives: Assessment of water quality on the basis of microbiological and physico-chemical properties from different sources of water from selected regions of Meghalaya i.e., from stream, spring, groundwater, well water, PHE UV treated water and drill water(raw). Study Design: This study was conducted on six different samples from stream, spring, groundwater, well water, PHE UV treated water and drill water(raw) respectively at State Food testing laboratory, Meghalaya which is accredited by National Board for Testing and Calibration Laboratories (NABL- A constituent board of Quality Council of India). Methods: Microbiological methods include IS 15185:2002 for detection of E.coli, IS 5402:2012 method for detection of Standard Plate Count and IS 5403:1999 for detection of Yeast and mould and basic physicochemical methods from FSSAI manual for detection of pH, Total hardness, total alkalinity, Calcium magnesium, chloride and samples appearance. Results: In this study; it was observe that PHE UV treated water depicts absence of bacterial & fungal growth, also passes physio-chemical parameters as per IS:10500. Conclusion: On microbiological & physicochemical analysis, it was found that PHE UV treated water is the only source of water fit for consumption.